Application of the Discovery Learning Model to Improve Student Learning Outcomes in the Pancasila Education Subject - Marlena; Aulia, Nisa (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2025)
This study aims to improve student learning outcomes using the Discovery Learning method, in class IV of Elementary School 52/IX Leban Karas, student learning outcomes are still relatively low in the Pancasila Education subject, totaling 20 people during the pre-cycle. This study is a Classroom Action Research (CAR) consisting of 2 cycles. This study uses data collection instruments in the form of observations in the form of observation sheets, interviews conducted with teachers and students, questions, and documentation. This study also covers three domains, namely the cognitive domain, the affective domain, and the psychomotor domain according to the title, namely about learning outcomes. The results of this study indicate an increase in student learning outcomes using the Discovery Learning model with a percentage of average student learning outcomes in the pre-cycle of 52.17%, cycle I 73.95%, and cycle II 90% with a very high student learning outcome category, and the percentage of student success in the pre-cycle 62.5%, cycle I 87.5%, and cycle II 93.75% with a very high student learning outcome category. As well as an increase in teacher and student activity in cycle 1 of 25% and cycle 6.25%.